2003
DOI: 10.1113/jphysiol.2003.043034
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐Gated Na+ Channel Activation Induces Both Action Potentials in Utricular Hair Cells and Brain‐Derived Neurotrophic Factor Release in the Rat Utricle During a Restricted Period of Development

Abstract: The mammalian utricular sensory receptors are commonly believed to be non‐spiking cells with electrical activity limited to graded membrane potential changes. Here we provide evidence that during the first post‐natal week, the sensory hair cells of the rat utricle express a tetrodotoxin (TTX)‐sensitive voltage‐gated Na+ current that displays most of the biophysical and pharmacological characteristics of neuronal Na+ current. Single‐cell RT‐PCR reveals that several α‐subunit isoforms of the Na+ channels are co‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 43 publications
7
63
0
Order By: Relevance
“…This developmental excitability, also observed in the mouse utricle (Geleoc et al, 2004), has also been reported in other sensory organs of the higher vertebrates, such as the cochlea (Evans and Fuchs, 1987;Kros et al, 1998) and the retina (Pan and Hu, 2000;Kawai et al, 2001). Although, in most cases, the physiological relevance of the I Na remains unknown, we first reported that I Na was involved in the activity-dependent secretion of brain-derived neurotrophic factor (BDNF) in the neonate rat utricle (Chabbert et al, 2003). Regarding the major role of BDNF in the establishment and the stabilization of synaptic contacts (Ernfors et al, 1995;Schimmang et al, 1995), we proposed that the transient hair cell excitability may contribute to the synaptogenesis process in the vestibular organs.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…This developmental excitability, also observed in the mouse utricle (Geleoc et al, 2004), has also been reported in other sensory organs of the higher vertebrates, such as the cochlea (Evans and Fuchs, 1987;Kros et al, 1998) and the retina (Pan and Hu, 2000;Kawai et al, 2001). Although, in most cases, the physiological relevance of the I Na remains unknown, we first reported that I Na was involved in the activity-dependent secretion of brain-derived neurotrophic factor (BDNF) in the neonate rat utricle (Chabbert et al, 2003). Regarding the major role of BDNF in the establishment and the stabilization of synaptic contacts (Ernfors et al, 1995;Schimmang et al, 1995), we proposed that the transient hair cell excitability may contribute to the synaptogenesis process in the vestibular organs.…”
Section: Introductionsupporting
confidence: 61%
“…We have previously shown that, at birth [postnatal day 0 (P0)], rat utricle hair cells transiently express a neuronal-like tetrodotoxin (TTX)-sensitive voltage-gated Na ϩ current (I Na ), enabling these cells to generate sodium-driven action potentials (APs) (Chabbert et al, 2003). I Na is downregulated during the first postnatal week, decreasing the sodium-based excitability in mature hair cells.…”
Section: Introductionmentioning
confidence: 99%
“…We did not see the mixed Ca 2+ -Na + spikes that are typical of mouse IHCs in the first postnatal week (Marcotti et al, 2003b). All Atoh1 + cells lacked the voltage-gated Na + currents of immature HC subtypes (Chabbert et al, 2003;Eckrich et al, 2012;Géléoc et al, 2004;Li et al, 2010;Marcotti et al, 2003b;Oliver et al, 1997;Witt et al, 1994;Wooltorton et al, 2007). Again, these channels either were never expressed or had stopped being expressed by the earliest time point we examined, 12 days of in vitro differentiation.…”
Section: Voltage-gated Currents In Differentiated Hair Cell-like Cellsmentioning
confidence: 72%
“…It is therefore likely that ES cell types will have to be cotransplanted with appropriate factors to encourage directed differentiation and integration. It is known that neurotrophic factors are important for hair cell development (Chabbert et al 2003), and a recent report indicates that epidermal growth factor (EGF) may be required to induce formation of new hair cells (Doetzlhofer et al 2004). The formation of new hair cells may also require overexpression of Math1, a transcription factor downstream in the EGF pathway that is essential for hair cell development (Zheng and Gao 2000;Woods et al 2004).…”
Section: Discussionmentioning
confidence: 99%